2006
DOI: 10.1063/1.2385180
|View full text |Cite
|
Sign up to set email alerts
|

Origin of efficient luminescence from GaN:Eu3+ epitaxial films revealed by microscopic photoluminescence imaging spectroscopy

Abstract: We have studied photoluminescence ͑PL͒ properties of Eu 3+ -doped GaN ͑GaN:Eu 3+ ͒ epitaxial films by microscopic PL imaging spectroscopy. The GaN : Eu 3+ epitaxial films exhibit efficient red luminescence related to intra-4f transitions of Eu 3+ ions. The intensity and the spectral shape of the Eu 3+ -related PL are sensitive to the Eu 3+ concentration, the excitation wavelength, and the monitored position. Microscopic PL imaging spectroscopy revealed that efficient red luminescence of GaN : Eu 3+ epitaxial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…The intensity of the PL due to the Eu 3+ ions is sensitive to the monitored position; the several bright spots and dark area are clearly observed. Similar inhomogeneous PL intensity images are also obtained at room temperature [14]. In our microscopic PL imaging spectroscopy experiments at room temperature [14], it has been concluded that the intensity of the Eu 3+ ions is sensitive to local environment of Eu 3+ ions and that the Eu 3+ ions exhibit efficient luminescence when they are incorporated into distorted Ga lattice sites around the point defects and dislocations introduced by the doping of Eu 3+ ions.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The intensity of the PL due to the Eu 3+ ions is sensitive to the monitored position; the several bright spots and dark area are clearly observed. Similar inhomogeneous PL intensity images are also obtained at room temperature [14]. In our microscopic PL imaging spectroscopy experiments at room temperature [14], it has been concluded that the intensity of the Eu 3+ ions is sensitive to local environment of Eu 3+ ions and that the Eu 3+ ions exhibit efficient luminescence when they are incorporated into distorted Ga lattice sites around the point defects and dislocations introduced by the doping of Eu 3+ ions.…”
Section: Resultssupporting
confidence: 65%
“…Space-resolved photoluminescence (PL) spectroscopy is one of the most useful methods for understanding of the nature of impurity luminescence and energy transfer mechanism in impurity-doped semiconductors [12][13][14]. In the previous report [14], we have revealed that the efficient red luminescence is attributed to the Eu 3+ ions located around point defects and * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the incorporation of Eu ions inside the GaN NCs' core changes their lattice constant, which should induce strain, 23 which, in turn, creates more defect states ͑increasing visible intensity͒. Moreover, for the GaN film, Ishizumi et al 24 have observed that Eu 3+ -ion doping induces stacking faults and twins with the dislocations in the GaN host crystal and that the distortion of the crystal lattice occurs over the entire GaN:Eu 3+ films as a result of these dislocations.…”
Section: K34mentioning
confidence: 97%
“…This also applies for solar cells, and simultaneous observation of PC and PL, with extension to time-resolved or microscopic techniques have been performed successfully [21]- [26]. For excitation we use two wavelength tunable sources, and an infrared laser diode with a fixed wavelength.…”
Section: Sample Structure and Experimental Setupmentioning
confidence: 98%